Marine trophic niche use and life history diversity among Arctic charr Salvelinus alpinus in southwestern Greenland. Issue 3 (10th February 2020) - Davidsen, Jan G.; Power, Michael; Knudsen, Rune; Sjursen, Aslak D.; Kjærstad, Gaute; Rønning, Lars; Arnekleiv, Jo V.
Abstract: Life history strategies and potential marine niche use of Arctic charr Salvelinus alpinus ( n = 237, 84–652 mm, total body length, L T ) were determined during the ice‐free season (2012) at three different watercourses in south‐western Greenland. All Arctic charr were collected from freshwater habitats. Based on stable isotopes of δ 34 S, the Arctic charr were categorized as either marine‐ or freshwater‐dependent feeders. The use of time‐integrated trophic tracers (stable isotopes of δ 13 C, δ 15 N, δ 34 S) suggested that several trophic groups of Arctic charr operate alongside within each fjord system. The groups suggested were one group that specialized in the marine habitat, in addition to two freshwater resident morphs (small‐sized resident and/or large‐growing cannibalistic individuals). Stomach contents consisted entirely of freshwater and terrestrial prey ( i.e., insects), indicating that marine‐dependent feeders also fed in freshwater habitats after return from their marine migration. Growth and maturity patterns further supported variable life history strategies within each watercourse. The life history strategy patterns and marine trophic niche use were consistent across the watercourses along several hundred kilometres of coastline. This study represents the first ecological baseline for partially anadromous populations of Greenland Arctic charr.